A pathway to earlier discharge following TAVI: Assessment of safety and resource utilization. Issue 1 (23rd May 2015) - Noad, Rebecca L.; Johnston, Nicola; McKinley, Andrew; Dougherty, Mark; Nzewi, O.C.; Jeganathan, Reuben; Manoharan, Ganesh; Spence, Mark S.
Abstract : Introduction: There is considerable variability within the population of patients treated with transcatheter aortic valve implantation (TAVI), the procedural approach and time to discharge. In Belfast, from the commencement of our program, our approach has been to perform TAVI by the least invasive approach, where feasible, utilizing a percutaneous transfemoral route and local anesthetic. By analyzing our Belfast TAVI database we identified factors that predicted shorter admission times without impacting adversely on patient safety. Following this, we developed an early discharge pathway. The aim of this current study was to perform a prospective analysis of outcomes in our unit since implementation of this pathway assessing discharge time, mortality, serious adverse events, readmission, and resource implications for patients according to time to discharge. Methods: Consecutive patients who underwent TAVI and were successfully discharged from 2013 to 2014 over a 14 month period were included, and analyzed according to time to discharge. Baseline and procedural characteristics, mortality, serious adverse events, readmission, and cost were assessed. Results: In total 120 patients were included, 26 (21.7%) were discharged the same/next day, 39 (32.5%) early (>1–4 days), and 55 (45.8%) discharged in the late group. There was no significant difference in baseline or preprocedural characteristics. The incidence of complications was low, and there was no difference in 30‐day mortality ( P = 0.167) or readmission rates between groups ( P = 0.952). Resource analysis revealed the late discharge group cost £3, 091.6 more per patient per TAVI than same/next day discharge group. Conclusion: Same/next day discharge can be performed safely in appropriately selected patients. Although this will be achieved in a minority of patients (21.7% in this study using an early discharge pathway) it has potential for resource and cost savings. © 2015 Wiley Periodicals, Inc.